How dots behave in two different pitch sizes? Analysis of tactical behavior based on position data in two soccer field sizes - Filipe Manuel Clemente (RICYDE. Revista Internacional de Ciencias del Deporte, 2018)
The purpose of this study was to analyze the effects of two different field sizes (full and half of an official size field) on the tactical behaviors measured by position data of players. Ten amateur soccer players (age = 23.39 ± 3.91 years old) were tracked with GPS units during two situations of 11 vs. 11, one in each field size. The position data was treated and the centroid and stretch index of the team were calculated with the Ultimate Performance Analysis Tool. Significantly greater values of centroid in goal- to-goal axis (p = 0.001; ES = 3.794), centroid in lateral-to-lateral axis (p = 0.001; ES = 0.729) and total stretch index (p = 0.001; ES = 1.185) were found in the full-size game. The full-size of the field increased the distances between teammates and the distances to the centroid. Moreover, the position of geometrical center of the team was beyond of the middle line in the full size.